Marija Makarovič - Žagar, Janja (Etnolog. Nova vrsta (Ljubljana), 2000)
On the occasion of Dr. Marija Makarovič's jubilee the article presents her achievements in the Slovene Ethnographic Museum. It is primarily a presentation of her fundamental museum work: collecting and documenting objects, written, pictorial and oral material, and its professional processing through museum exhibitions.
Keywords: Makarovič, Marija, 1930-; biografije; ethnology; etnologija; Slovenski etnografski muzej